FORMS OF THE POTENTIAL OF COTTON-TEXTILE CLUSTERS IN THE SUSTAINABLE DEVELOPMENT OF THE REGION - Xayitov , Rustam (INTERNATIONAL CONFERENCE ON MODERN RESEARCH AND SCIENTIFIC INNOVATION, 2026)
This article discusses the content and existing forms of the potential of cotton-textile clusters in the sustainable development of the region. Also, conclusions are drawn on the effective use of the forms of potential of cotton-textile clusters.